Study Literature Peran Epidermal Growth Factor dalam Proses Penyembuhan Luka - Nur Febrianti; Takdir Tahir; Saldy Yusuf (Jurnal Keperawatan Muhammadiyah, 2019)
Background: Wounds occur when normal skin structures are damaged. Injury events in Indonesia have increased by 8.2% and the highest prevalence in South Sulawesi is 12.8%. One of the growth factors that play a role in the wound healing process is epidermal growth factor (EGF). EGF includes polypeptides that contain 53 amino acids, and EGF is present in all fluids in the body and platelets. This review aims to determine the role of EGF in the process of wound healing. Method: Data collected since 2017 using 8 databases (pubmed, science direct, google schollar) where the literature used is internationally published literature, additional references are taken from the bibliography of all relevant articles, all relevant articles are reviewed and analyzed. Results: EGF has a role in wound healing. EGF increases motility and epithelial cell migration. EGF can stimulate cell growth, proliferation and differentiation by binding to high affinity to the EGF receptor (EGFR) on the cell surface. The goal of EGF healing is most epithelial tissue, fibroblasts, and endothelial cells. EGF can call three important biological actions in tissue repair including cytoprotection, mitogenesis, and migration. Conclusion: EGF plays an important role in the wound healing process, especially in the re-epithelial process. Based on this review, it is suggested that the selection of dressings that are used should support EGF.